Availability of social services for families with disabled children in the context of the welfare state - Raišienė, Agota Giedrė; Gardziulevičienė, Laura (Socialiniai tyrimai, 2021)
The phenomenon of the welfare state is characterized by complexity of indicators. To determine in which areas the country is closer to the welfare state, various areas of social policy are analysed. In this article, we set out to investigate one of them, i.e., the accessibility of social services for children with disabilities.The European Union ensures the basic preconditions for the well-being of children with disabilities and emphasizes the compatibility of health, social and educational services (European Commission, 2021). In addition, Member States are free to introduce specific measures for social inclusion (COM, 2021). The well-being of children with disabilities is inseparable from that of adults, usually the family in which the children live. Depending on the child’s disability, the family has to devote time to the child’s special needs, so opportunities to function in society, such as working and earning an income, become dependent on the social assistance received for the disabled child. Research shows that participation in labour market processes reduces the social exclusion of families with children with disabilities and improves quality of life indicators in general (Stefanidis & Strogilos 2020). However, analysis of good practice is more common, while information about the lack of services that parents face difficulties remains overboard. Thus, our research contributes to a better understanding of how families raising children with disabilities use state-provided social services and what solutions and measures are needed to improve the quality of life of children with disabilities and their relatives. The practical implications of our article are revealed through the possibility of more confidently shaping the decisions and measures of the welfare state.The article presents results of a survey of 68 families with disabled children. Our research was conducted in Druskininkai municipality which has typical infrastructure of social services for the disabled and their families in Lithuania.Our study has shown that social services in Lithuania poorly meet needs of families with disabled children. Though social inclusion is one of the most important features of the welfare state, the provision of social services to disabled and their families goes beyond the concept in Druskininkai municipality at least. Families have little information about social guarantees and support provided by the state and municipality. The families are limited to services reported by health care and education institutions. Moreover, the most significant problem hindering social integration of disabled and their families is a small portion of disabled children using services of day care centre. As a result, children suffer at risk of social exclusion while disabled children’s parents lack of opportunities to fully participate in the labour market.Based on the results of the study we state that increasing the availability of social services that meet the needs of families with disabled children is a necessary social policy solution, without which the development of a welfare state in Lithuania is hardly possible.
Keywords: disabled children; social services; families; social inclusion; welfare state